Determination of homozygous susceptible strain in Culex quinquefasciatus (Say), using single raft sib-selection method. - Hidayati, H.; Nazni, W.A.; Mohd, S.A. (Malaysian Society of Parasitology and Tropical Medicine, 2008)
The standard laboratory strain was found to be heterozygous for susceptibility. Hence, an attempt was made to obtain a homozygous susceptible strain in Culex quinquefasciatus (Say) using single raft sib-selection method. Lab-bred females of Cx. quinquefasciatus from insectariums, Unit of Medical Entomology were used in the experiment. After blood feeding Cx. quinquefasciatus mosquitoes laid eggs in raft form, ten rafts selected randomly for the test. Each egg raft was introduced into a plastic tray from number one to number ten. Twenty-five third stage larvae from each tray were exposed to 17.5 microl from 500mg/l malathion in a paper cup label number 1 to number ten. In the bioassay, which had 100% mortality, the respective larva in that particular tray was bred to adult stage for the following generation. Less than 7days old female mosquitoes that emerged from F(0) were used in the test. The F(0) and the subsequent adult and larval stage generations were subjected to adult and larval bioassay. After selection for about 10 generations, a homozygous susceptible strain in Cx. quinquefasciatus was obtained.